Thomas and Lady Hatt's Birthday Party - The Rev. W. Awdry (London, United Kingdom Egmont UK Ltd, 2010)
The Fat Controller is going to Lady Hatt's party. But when two cars break down, a steamroller crashes and a fireman falls ill, he wonders if he will ever get there. Thomas is determined to help.
Keywords: Thomas Section